(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study aims to analyse the efficacy of pricing public goods and services in producing public revenues and supporting public expenditures in Egypt from 2010 to 2019. Utilising a comprehensive scientific methodology incorporating a comprehensive literature review, quantitative analysis, and inductive reasoning, this study aims to examine the hypothesis suggesting a correlation between fiscal policy and the pricing of public goods and services. The findings indicate that the pricing mechanisms employed for specific categories, such as taxes on income and profits, customs charges, power tariffs, and fees for housing and building services, exhibit a lack of efficacy in generating public revenues. The pricing mechanism seems to diverge from financial policies aimed at increasing public revenues through the acquisition of more cash, as indicated by an evaluation of the historical importance of income streams obtained from the pricing of public goods and services. The percentages of contribution are rather tiny, which do not sufficiently cover public expenditures or have a substantial impact on the GDP. The results provide evidence in favour of the theoretical proposition positing a connection between fiscal policy and the pricing of public goods and services in Egypt. The study concludes by providing valuable insights into fiscal policy that could be of significance to governmental authorities.